Building a sustainable sweetpotato seed system in Malawi: Experiences from the "Rooting out hunger in Malawi" project. - Abidin, P.E.; Chipungu, Felistus P.; Benesi, I.R.M.; Mwenye, O.; Todd, R.; Thomas, J.; Chimsale, R.; Daudi, A.; Nkhomam, P.; Mkumbira, J.; Botha, B.; Carey, E.E. (2012)
The project “Rooting out Hunger in Malawi with Nutritious Orange-Fleshed Sweetpotato (OFSP)” was launched in October 2009 for the benefit of women and children in the country. This 4.5-year effort targets 115,000 households to improve vitamin A and energy intake using improved sweetpotato varieties. It also seeks to boost yields by 50% and improve incomes by 20%. The project aligns with the Agriculture Sector Wide Approach to food and nutrition security and crop diversification. With Irish Aid support, CIP initially worked in partnership with government agencies and three NGOs as implementing partners (IPs) and targeted 4 districts. The project established a “1-2-3” seed multiplication system, with clean planting material produced at a primary multiplication site, and decentralized vine multiplication sites (DVMs) doing multiplication at the community level. DVMs run by individuals or groups of farmers with access to irrigation were established by the IPs and supervised by district Extension staff. Mutiplication at the DVMs was termed secondary (vine production using rapid multiplication) or tertiary (production of both roots and vines, particularly during the hungry season). A subsidized voucher system was used by partners to allow at-risk households to purchase sweetpotato planting material from DVMs. Promotion and awareness campaigns were conducted in each district to stimulate demand for OFSP. By February 2012, the project had reached 36,403 households in 5 districts with subsidized vouchers, and an additional 19,331 beneficiaries through non-voucher sales. Seven IPs in 14 districts partnered in the effort. Lessons learned and sustainability of the system will be discussed.